Willingness to use pre-exposure prophylaxis among Black and White men who have sex with men in Atlanta, Georgia - Rolle, Charlotte-Paige (Int J STD AIDS, 2016)
PrEP willingness may be different among black and white men who have sex with men (MSM) given known disparities in HIV incidence, sociodemographic factors, and healthcare access between these groups. We surveyed 482 black and white HIV-negative MSM in Atlanta, GA about their willingness to use pre-exposure prophylaxis (PrEP) and facilitators and barriers to PrEP willingness. Overall, 45% (215/482) of men indicated interest in using PrEP. Engaging in recent unprotected anal intercourse (UAI) was the only factor significantly associated with PrEP willingness in multivariate analyses (OR 1.73, 95% CI 1.13, 2.65). Willing men identified “extra protection” against HIV as the most common reason for interest in using PrEP, whereas unwilling men most commonly cited not wanting to take medication daily, and this reason was more common among white MSM (42.3% of white MSM vs. 28.9% of black MSM, f> = 0.04). Most men indicated willingness to use PrEP if cost was <50 dollars/month; however, more black MSM indicated willingness to use PrEP only if cost were free (17.9% of white MSM vs. 25.9% of black MSM, p = 0.03). Overall, these data are useful to scale up PrEP interventions targeting at-risk MSM in Atlanta and highlight the need for implementation of low cost-programs, which will be especially important for black MSM.